MiRNAs in Urine Extracellular Vesicles as Predictors of Early-Stage Diabetic Nephropathy. (28th January 2016) - Jia, Yijie; Guan, Meiping; Zheng, Zongji; Zhang, Qian; Tang, Chuan; Xu, Wenwei; Xiao, Zhizhou; Wang, Ling; Xue, Yaoming
Abstract : Background . miR-192, miR-194, and miR-215 are enriched in the kidney and play roles in the pathogenesis of diabetic nephropathy (DN). Extracellular vesicles (EVs) can be detected in body fluids and may serve as disease biomarkers. Methods . Eighty type 2 diabetes patients with normoalbuminuria (n = 30 ), microalbuminuria (n = 30 ), or macroalbuminuria (n = 20 ), as well as 10 healthy controls, were enrolled in this study. Real-time PCR was used to evaluate urinary EV miRNAs expression. Results . The miR-192 levels were significantly higher than the miR-194 and miR-215 levels in urine EVs and all three miRNAs were significantly increased in the microalbuminuric group compared with the normoalbuminuric and control subjects but were decreased in the macroalbuminuric group. In patients with normoalbuminuria and microalbuminuria, miR-192 was positively correlated with albuminuria (r = 0 . 357, P = 0.0 05 ) levels and transforming growth factor- (TGF-) β 1 (r = 0 . 356, P = 0.0 05 ) expression. Receiver operating characteristic (ROC) curve analysis revealed that miR-192 was better than miR-194 and miR-215 in discriminating the normoalbuminuric group from the microalbuminuric group. Exposure of human renal tubular epithelial cells to high glucose increased the expression of both miRNAs in cellular supernatant EVs, indicating a potential source. Conclusion . These results suggest the potential use of urinary EV miR-192 as a biomarker of the early stage of DN.